A REVIEW STUDY OF DIGI STRATEGIC POSITIONING IN CONFRONTATION OF DISRUPTIVE TECHNOLOGY - Laith Ali Zgair Gharan; Baraa Shaalan Amir; Oday Lateef Mahmood (Scholars Digest Publishing, 2025)
The introduction of new technology is considered disruptive when technology changes the market structure and the ways that the business operates. Smartphone and its associated technology such as Apps have disrupted the communication industry. Telecommunication companies have to response to this challenge and reposition themselves to gain competitive advantage. The aim of this study is to identify the way that DiGi Company responded to the disruptive technology of the smartphone and its application. The study reviewed the literature to find the responses of disruptive technology. Further, the paper reviewed the profile of the company and based on that, the paper derived the findings of the study. The findings show that DiGi has responded professionally and reposition itself to maintain its revenue and to survive and thrive. Discussion of the findings and recommendations are given.